2019
DOI: 10.1140/epjc/s10052-019-6923-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal radiation and inclusive production in the CGC/saturation approach at high energies

Abstract: In this paper, we discuss the inclusive production of hadrons in the framework of the CGC/saturation approach. We argue, that gluon jet inclusive production stems from the vicinity of the saturation momentum, even for small values of the transverse momenta pT . Since in this region, we theoretically, know the scattering amplitude, we claim that we can provide reliable estimates for this process. We demonstrate, that in a widely accepted model for confinement, we require a thermal radiation term to describe the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…α S denotes the running QCD coupling, ∇ 2 T the Laplace operator with respect to r, it is equal to ∇ 2 T = 1 r d dr r d dr . In our paper [2] we found that the main contribution at high energies stem from the specific kinematic region in the vicinity of the saturation scale. Indeed, at high energies and sufficiently small values of p T the dipole amplitudes are in the saturation region, where the parton densities are large and the dipole scattering amplitude displays geometric scaling behaviour, being a function of only one variable: τ = r Q s (W, b) [28][29][30].…”
Section: A General Formulaementioning
confidence: 57%
See 4 more Smart Citations
“…α S denotes the running QCD coupling, ∇ 2 T the Laplace operator with respect to r, it is equal to ∇ 2 T = 1 r d dr r d dr . In our paper [2] we found that the main contribution at high energies stem from the specific kinematic region in the vicinity of the saturation scale. Indeed, at high energies and sufficiently small values of p T the dipole amplitudes are in the saturation region, where the parton densities are large and the dipole scattering amplitude displays geometric scaling behaviour, being a function of only one variable: τ = r Q s (W, b) [28][29][30].…”
Section: A General Formulaementioning
confidence: 57%
“…For completeness of presentation, in this subsection we give a brief review of our theoretical and phenomenological approach to the contribution of the dipole-nucleon scattering amplitude to the inclusive gluon production, that has been discussed in Ref. [2].…”
Section: B Dipole-nucleon Scattering Amplitudementioning
confidence: 99%
See 3 more Smart Citations